"Nudge" and the epidemic of missed appointments: Can behavioural policies provide a solution for missed appointments in the health service?. Issue 4 (20th June 2016) - Aggarwal, Ajay; Davies, Joanna; Sullivan, Richard
Abstract : Purpose: – Missed appointments constitute a significant problem in the UK National Health Service (NHS) and this remains an area where improvements could yield substantial efficiency savings. The purpose of this paper is to suggest that nudge policies based on behavioural theories may help target interventions to improve patient motivation to attend appointments. Design/methodology/approach: – The authors propose two policies to reduce missed appointments. The first attempts to empower patients through making the appointment system more individualised to them and utilising their intrinsic feelings of social responsibility. The second policy utilises a financial commitment given by the patient at the time of booking. The different mechanisms of influencing patient behaviour are based on two different views of what motivates individuals' actions. The first policy is based on individuals being "knights". They are altruistic and have well-intentioned values. The second policy option is constructed on the premise that an individual is governed by self-interest, and they are in fact "knaves". Findings: – A policy, which avoids the use of financial penalties is likely to be more culturally acceptable within the NHS. It could also prevent the phenomenon of "crowding out" whereby the desire to act dutifully gets displaced by the motivation to avoid incurring a monetary fine. Originality/value: – Testing both strategies would provide insight into patient attitudes towards health care and society. This would help optimise behavioural strategies which may influence not only appointment attendances but also have wider implications for encouraging rational health care consumption.